Global disparity in breast cancer screening guidelines- Is there a need for an individualized approach for breast cancer screening? - Qazi, Almasudin (LIAQUAT MEDICAL RESEARCH JOURNAL, 2022)
Breast cancer screening is the key to better clinical outcomes. Cancer diagnosed at the stage where it is still within the ducts has the highest potential for best survival. A screening mammogram is a key for early detection. However, there is variation in the age guidelines for starting the screening and cessation. Given the rate of breast cancer in the region, the government’s economic resources and the priority of the screening service all play a role. Developed countries have benefited from screening mammogram facilities and improved disease outcomes, but underdeveloped countries have not yet developed national screening programs. Thus nations must take the incidence of the biology of breast cancer into account and make evidence-based